2017
DOI: 10.1111/jpc.13777
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and cost of hospitalisation of children with injuries from playground equipment falls in New South Wales, Australia

Abstract: Rates of hospitalisation of children for playground fall injuries remain high despite implementation of national playground safety standards in Australia. This research highlights where interventions should be targeted to reduce the incidence and burden of injuries following falls from playground equipment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 35 publications
4
21
0
Order By: Relevance
“…[16][17][18] Considering the physical structure of the schools, it was found that students from schools that have patios with soft floors, such as sand and grass, had a lower prevalence of TDI when compared to students from schools where the patio floor was cement. Some authors have emphasized that play spaces for children (playgrounds, patios, and sports courts) should have soft floors to reduce the occurrence and severity of unintentional injuries 14,26 and of dental trauma, specifically. 2,12,27 Nevertheless, the findings regarding the patio floor obtained in the present study should be interpreted with caution, since only a school had a patio floor of grass, and only one school had a patio floor of sand.…”
Section: Upper Lower Total [N (%)] C/inc [N (%)] L/inc [N (%)] C/inc mentioning
confidence: 99%
“…[16][17][18] Considering the physical structure of the schools, it was found that students from schools that have patios with soft floors, such as sand and grass, had a lower prevalence of TDI when compared to students from schools where the patio floor was cement. Some authors have emphasized that play spaces for children (playgrounds, patios, and sports courts) should have soft floors to reduce the occurrence and severity of unintentional injuries 14,26 and of dental trauma, specifically. 2,12,27 Nevertheless, the findings regarding the patio floor obtained in the present study should be interpreted with caution, since only a school had a patio floor of grass, and only one school had a patio floor of sand.…”
Section: Upper Lower Total [N (%)] C/inc [N (%)] L/inc [N (%)] C/inc mentioning
confidence: 99%
“…Although males account for almost two‐thirds of hospitalised head injuries, the hospitalised rate of head injuries has significantly increased among females. The increased hospitalisation rates in younger children and females may be related to a number of factors which have previously been identified in the literature including increased scooter use, falls, and/or reduced adult supervision due to a false sense that play equipment with safety features (eg, trampoline enclosures and padding) is risk‐free …”
Section: Discussionmentioning
confidence: 99%
“…Falls typically occurred in children aged <1 year, while being carried or supported by other persons, or from furniture, indicating a need for greater awareness of fall injury prevention and safety amongst caregivers . Falls from playground equipment are a common cause of head injury for children . Head injury prevention strategies for playgrounds include the introduction of impact absorbing surfaces, the introduction of a maximum free‐height of fall of 1.5 m and the introduction of safety features such as trampoline enclosures …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the number of falls in children has increased and there has been no change in the incidence of events such as major trauma [6]. Furthermore, existing measures focus solely on prevention, not on mitigating the outcomes of an unintentional fall once it takes place [7,8]. Although physical education (PE) classes can improve balance, they do not teach children to modify their natural motor responses to render them safer in the event of a fall [9,10].…”
Section: Introductionmentioning
confidence: 99%